KEMAMPUAN KOMUNIKASI MATEMATIS DAN HABITS OF MIND MAHASISWA PADA MATERI LINTASAN TERPENDEK MENGGUNAKAN ALGORITMA FLOYD WARSHALL - Arina Syukria (Jurnal Peluang, 2012)
Abstract This study aims to determine the mathematical communication skills and habits of mind students and obtains a description of the obstacles faced by the students in using Floyd Warshall algorithm software on shortest path subject. This study is a qualitative research-description. The samples are 4 students of  Teacher Education Mathematics Faculty Unsyiah who take courses Graph Theory on academic year 2012/2013. The subjects was choosen based on the observation who are active, less active and not active students in the learning, and also GPA more than three. The data were obtained from observations, interviews and written responses of research subjects. Mathematical communication skills of students who studied as follows, subject I has fair mathematical communication skills, subject II has very good mathematical communication skills, subjects III has  good mathematical communication skills, and subjects IV has a fair mathematical communication skills. Habits of Mind research subjects is shown as follows; Habits of mind subject I included into the fair category. Habits of Mind of subjects II included into the excellent category, whereas habits of mind of subject III included into the very good category. Last habits of mind of subjects IV included into the fair categori. The obstacles faced by students in the use of software constraints Floyd Warshall algorithm on shortest path is, 1 ) graph / digraph can not be repaired when it is processed, 2 ) do not work can not be stored, 3 ) vertices that can be used is limited, and 4 ) no distance information between one place to another, so less can be used in real life. Keywords: mathematical communication skills, habits of mind, shortest path, Floyd Warshall Algorithm.